A luminescent turn-up metal–organic framework sensor for tryptophan based on singlet–singlet Förster energy transfer. Issue 31 (31st July 2018) - Zhang, Jun; Huang, Yike; Yue, Dan; Cui, Yuanjing; Yang, Yu; Qian, Guodong
Abstract : A highly stable MOF, ZJU-108, was synthesized with Zn 2+ and 6-(4-pyridyl)-terephthalic acid (H2 pta) as construction units, and it exhibits an impressive turn-on luminescence enhancement response to tryptophan. Abstract : A water stable metal–organic framework, ZJU-108, was designed and successfully synthesized as a luminescent turn-up sensor, and it can discriminate tryptophan from other natural amino acids in aqueous solution. Because of the apparent lower singlet level of tryptophan compared with other amino acids, the singlet–singlet Förster energy transfer mechanism was applied to design a luminescent sensor. As a result, a selective MOF sensor for tryptophan was realized by choosing the ligand with the appropriate singlet energy level. As expected, ZJU-108 shows an excellent luminescence enhancement response to tryptophan over other natural amino acids with a detection limit of 42.9 nM. This work presents a new insight for designing turn-up MOF sensors and demonstrates the potential of ZJU-108 as a luminescent probe for the detection of tryptophan.